Sobre el texto: "PRÁCTICAS FÍSICODEPORTIVAS. ACTITUDES Y TENDENCIAS DE ESCOLARES COLOMBIANOS". (Atenas, 2024)
Sobre el texto: "PRÁCTICAS FÍSICODEPORTIVAS. ACTITUDES Y TENDENCIAS DE ESCOLARES COLOMBIANOS".